Assessing individual head and neck squamous cell carcinoma patient response to therapy through integration of functional and genomic data - Bottomly, Daniel; Mathieson, Chase; Vigoda, Myles; Jeng, Sophia; Evans, Nathaniel; Anderson, Ashley; Blucher, Aurora; Lesch, Aletha; Zheng, Christina; Laderas, Ted; Jacobs, James; Kulesz-Martin, Molly; et al. (Scientific reports, 2025)
Even though head and neck squamous cell carcinoma (HNSCC) is the seventh most common cancer worldwide, there are only two PD-1 targeted immunotherapies (pembrolizumab and nivolumab) and one tumor intrinsic EGFR targeted therapy (cetuximab) that are FDA approved for treatment of HNSCC. Taking advantage of a high throughput inhibitor assay and computational tools originally showing success in leukemia, we designed and employed HNSCC-specific inhibitor panels that capture the diversity of aberrational pathways in HNSCC to test viable cells derived from patients’ HNSCC tumors. This provides a functional context to the multi-omic readouts conducted on these samples (mutations, protein expression and copy number alterations). In addition to generating these deeply characterized functional genomics datasets, we also developed additional visual analytics that have the potential to provide greater insight into HNSCC drug response patterns and potentially aid precision oncology tumor boards in evaluation and assessment of effective targeted therapeutic agents.